Effects of angiotensin II, arginine vasopressin and tromboxane A2 in renal vascular bed: role of rho-kinase - Cavarape, Alessandro; Bauer, Johannes; Bartoli, Ettore; Endlich, Karlhans; Parekh, Niranjan (Nephrology, dialysis, transplantation, 2003)
Abstract. Background. Angiotensin II (Ang II), arginine vasopressin (AVP) and tromboxane A2 (TxA2) are dissimilar vasoconstrictors involved in regulating renal
Gesehen am 28.04.2021